THE CREATION OF ADVERTISING: VISION OF MUSIC (WITH REFERENCE TO AUDIO-VISUAL MEDIUM): विज्ञापन की सृष्टि: संगीत की दृष्टि (दृश्य-श्रव्य माध्यम के संदर्भ में) - Srivastava, Sushma (International Journal of Research -GRANTHAALAYAH, 2015)
Communication can be called synonymous with life. Millions of cells in our body constantly communicate among themselves. The moment this process stops, the moment we get to death. Another name of life is communication, communication-nothingness signifies death. In the current environment, there is a widespread level of communication, 'mass communication', that is, when we convey a sentiment or information to others and this process takes place on a collective scale, it is called 'mass communication'. In mass communication, there is a simultaneous contact between the sender and a large number of recipients and there is a possibility that most of the people receiving the information or information will have some reaction. संचार को जीवन का पर्याय कहा जा सकता है हमारे शरीर की लाखों कोशिकाएँ आपस में लगातार संचार करती रहती हैं। जिस क्षण यह प्रक्रिया बंद हो जाती है उसी क्षण हम मृत्यु को प्राप्त हो जाते हैं। जीवन का दूसरा नाम संचार संलग्नता है, संचार-शून्यता मृत्यु का द्योतक है। वर्तमान परिवेश में संचार का व्यापक स्तर है ‘जनसंचार‘ अर्थात जब हम किसी भाव या जानकारी को दूसरों तक पहुँचाते हैं और यह प्रक्रिया सामूहिक पैमाने पर होती है तो इसे ‘जनसंचार‘ कहते हैं। जनसंचार में प्रेषक तथा बड़ी संख्या में ग्रहणकर्ता के बीच एक साथ संपर्क स्थापित होता है एवं इस बात की संभावना बनी रहती है कि सूचना या जानकारी प्राप्त करने वाले लोगों में से अधिकांश में कुछ न कुछ प्रतिक्रिया अवश्य उत्पन्न होगी।